2015
DOI: 10.1007/s12070-015-0843-6
|View full text |Cite
|
Sign up to set email alerts
|

Timing for Removal of Asymptomatic Long-Term Ventilation Tube in Children

Abstract: Otitis media with effusion (OME) is the most frequent illness in children. Surgical treatment options include ventilation tube insertion, adenoidectomy or both. Opinions regarding the risks, benefits and intubation period of ventilation tube insertion vary greatly. To determine the appropriate time for when to remove asymptomatic longterm ventilation T-tubes in children. In this prospective study, we analyzed the results of 120 pediatric patients (6-12 years) (240 ears) with persistent OME; we employed the Goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…Notably, at about 18 months, 90% of placed tubes had spontaneously extruded and the rate of extrusion plateaued thereafter. The authors noticed increased complications as the duration of intubation increased (>12 months) similar to the findings of Abdel‐NabyAwad 1 . The OME recurrence rate significantly decreased after 12 months following spontaneous tube extrusion (11.2% vs. 21.9%).…”
Section: Literature Reviewsupporting
confidence: 74%
See 2 more Smart Citations
“…Notably, at about 18 months, 90% of placed tubes had spontaneously extruded and the rate of extrusion plateaued thereafter. The authors noticed increased complications as the duration of intubation increased (>12 months) similar to the findings of Abdel‐NabyAwad 1 . The OME recurrence rate significantly decreased after 12 months following spontaneous tube extrusion (11.2% vs. 21.9%).…”
Section: Literature Reviewsupporting
confidence: 74%
“…Abdel‐NabyAwad 1 performed a prospective study on 120 pediatric patients (240 ears) from 6 to 12 years old with persistent OME in whom Goode T‐tubes were employed. Patients were randomly divided into four groups according to the intubation period (6, 12, 18, and 24 months).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…281,282 One chart review 283 showed low rates of otorrhea, granulation tissue, and persistent perforation when tubes were removed after 2 to 3 years, but rates increased to >50% for all complications with intubation for 5 years or longer. A retained T-tube or other silicone tube can be easily removed in the office setting, 284 but a rigid grommet-type tube may require general anesthesia in an operative setting for removal.…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…This finding was consistent with the other studies that showed a higher recurrence rate once that extrusion time was less than 12 months. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%